Women Ulama in the Digital Era: Redefining Religious Authority in Muslim Communities - Mokodensoho, Sabil; Khoiriyah, Khoiriyah; Syam, Anna Rahma; Dara, Ravi (Yayasan Adra Karima Hubbi, 2025)
Background: The rapid expansion of digital media has transformed the landscape of religious communication in Muslim societies, challenging long-established patterns of religious authority that have traditionally been male-dominated. In this context, women ulama increasingly utilize digital platforms to disseminate knowledge, engage audiences, and negotiate their religious legitimacy within both local and transnational Muslim communities. Objective: This study aims to examine how women ulama in the digital era redefine religious authority, reshape modes of da‘wah, and construct new forms of credibility and influence in Muslim communities. Method: The research employs a qualitative approach, combining digital ethnography, content analysis of selected social media platforms, and in-depth interviews with prominent women ulama actively engaged in online religious discourse. Results: The findings reveal that digital spaces enable women ulama to bypass conventional institutional barriers, articulate alternative religious narratives, and build authority through expertise, ethical engagement, and interactive communication with followers. However, their authority remains contested, as they often face gender-based resistance, online harassment, and challenges from traditional religious institutions. Conclusion: The study concludes that digital media does not merely extend existing religious authority but actively reconfigures it, positioning women ulama as significant agents in the evolving ecology of Islamic knowledge and leadership in the digital era.